Hybrid Culture and Digital Innovation in Contemporary Performing Arts: A Case Study of Enda Walsh’s Disco Pig Performance at Brotherhood Bunker Bandung - Yuliana Hambuwali; Retno Dwimarwati; Wanda Listiani (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2026)
This study explores the contribution of video mapping technology and the use of non-conventional performance spaces in generating hybrid theatrical experiences in Enda Walsh’s Disco Pig, staged at the Brotherhood Bunker, Bandung. This production provides a significant case for examining the intersection of technology, spatial change and audience engagement as digital media gains a greater foothold in live performance in contemporary theatre. Data were collected through performance observation, visual documentation, and analysis of dramaturgical elements within a qualitative phenomenological approach. The results show that video mapping is not only a visual enhancement, but also a dramaturgical device that constructs memory, psychological landscapes and narrative transitions. In addition, transforming a nightclub basement into a performing space produces a hybrid spatiality that conflates entertainment, social interaction, and theatrical representation. The production also engages with broader concerns of urban identity, class relations, and spatial politics in contemporary digital culture. This study adds to theatre and performance studies by showing how digital technologies can extend dramaturgical practices and generate immersive experiences for the spectator in alternative performance settings. The findings provide theoretical insights into hybrid theatre and practical implications for artists and directors exploring digitally mediated performance.